PENILAIAN PENGAMANAN TEKNOLOGI PADA SISTEM PEMBELAJARAN ELEKTRONIK MENGGUNAKAN INDEKS KEAMANAN INFORMASI DI POLITEKNIK NEGERI BATAM - Muhammad Ramadhan Slamet; Febrina Wulandari; Diah Amalia (Politeknik Negeri Batam, 2019)
As an electronic learning system organizer State Polytechnic of Batam (Polibatam) must arrange secured electronic learning system. Ministry of Communication and Information of Indonesia expects the organizations which arrange electronic system can perform SNI ISO 27001 certification related to information security. Information security condition on organizations which will perform on certifiation is expected on maturity level at III+ (Directorate of Information Security Team, 2011). On the other hand, there is a gap between expected conditon and actual condition. Information security index (KAMI) is a tool to assess the implementation of information security that has been done. This research is assessed related to technology component because of high dependency of organization on technology. The purpose of research is to identify how far the security of technology at State Polytechnic of Batam by using information security index. Based on research, electronic learning system that is organized by State Polytechnic of Batam is low categorized. The total percentage is 65 or 54,17% out of maximum percentage. Therefore, the maturity level of technology security is on maturity level II which means the maturity level of technology security is under the expected maturity level for minimum readiness certification on III+. It is caused the position of State Polyetechnic of Batam is on a organizational development stage. Moreover, the focus of organization is related on operational, not strategic.